Sol-gel derived PZT and PZTN ceramics: A role of sintering temperature - Chontira Sangsubun (2018)
PZT and Nb-doped PZT (PZTN) ceramics were fabricated from triol sol-gel derived powders. The pellets were sintered at temperatures in the range of 1050-1200°C for 2 h. Coexistence of tetragonal and rhombohedral phases was clearly observed in PZT ceramics sintered at ≤1150°C, while PZTN ceramics showed coexistence of these phases at ≥1100°C. Densities of undoped PZT ceramics were rather low but could be improved by Nb addition. Grain growth inhibition was also observed in all PZTN samples. The dielectric constant was found to depend mainly on density of the ceramics. An addition of Nb dopant into PZT improved dielectric constant values regardless of sintering temperature. Copyright © Taylor & Francis Group, LLC.